The Verbal Participation in Arabic Language: A Linguistics Study - Garibeh, Alaa Taref (Arab Journal for Sciences and Research Publishing, 2020)
The purpose of this research is to study the verbal Participation in Arabic language, in terms of: its concept, the reasons for its occurrence, its types, and the position of some ancient and modern linguists, the researcher used the descriptive analytical method based on observation, induction and analysis. The research concluded that the verbal subscriber is a formal semantic issue that takes place at the level of the verbal, as it expresses in it one word for one or more meaning, and that it is a clear sign in the language, there is no way to deny it, even if the old and modern linguists disagreed about whether or not it occurred in the Arabic language.